Evaluación Físico-Mecánico de muestras de adobes de viviendas existentes en la provincia de Chimborazo. - Manotoa Cunalata, Lizbeth Natali (2022)
The present study intends to evaluate the physical-mechanical properties of samples of adobes from existing houses in the Province of Chimborazo, carried out in the following stages: sample collection, quantitative analysis, qualitative analysis and crossing of variables. Among the methodology, the field research method was applied for the collection of adobe samples, and technical-architectural survey of 13 vernacular houses. Second, the scientific method was applied with laboratory tests to test moisture content, sieving granulometry, liquid limit and plastic limit, and resistance of existing bricks. Finally, the qualitative data of the construction system were systematized and crossed with the quantitative variables. Among the findings, it is included that adobe is used around the Riobamba Canton, the adobe of the house with the highest resistance to compression was from Calpi with 0.5556 MPa and the one with the lowest resistance was from Punín with 0.0162 MPa, no house reaches the resistance established by the Peruvian Standard E. 080 of 1.0 MPa. Among the reasons for the low results is due to the place of extraction of the sample, most of which are directly exposed to climatic agents. It was possible to determine the state in which the house is located from the foundation to the roof, thus finding pathogenic agents that cause the deterioration of the property. Mostly the abandonment of the houses, without any maintenance, makes it possible not to maintain the adobe's resistance. These inputs will serve in the future for possible restoration or improvement of the adobe construction system in the Province of Chimborazo